Combined Organ Transplantation in Patients with Advanced Liver Disease - Zhang, Ingrid Wei; Lurje, Isabella; Lurje, Georg; Knosalla, Christoph; Schoenrath, Felix; Tacke, Frank; Engelmann, Cornelius (Seminars in Liver Disease, 2024)
Transplantation of the liver in combination with other organs is an increasingly performed procedure. Over the years, continuous improvement in survival could be realized through careful patient selection and refined organ preservation techniques, in spite of the challenges posed by aging recipients and donors, as well as the increased use of steatotic liver grafts. Herein, we revisit the epidemiology, allocation policies in different transplant zones, indications, and outcomes with regard to simultaneous organ transplants involving the liver, that is combined heart–liver, liver–lung, liver–kidney, and multivisceral transplantation. We address challenges surrounding combined organ transplantation such as equity, utility, and logistics of dual organ implantation, but also advantages that come along with combined transplantation, thereby focusing on molecular mechanisms underlying immunoprotection provided by the liver to the other allografts. In addition, the current standing and knowledge of machine perfusion in combined organ transplantation, mostly based on center experience, will be reviewed. Notwithstanding all the technical advances, shortage of organs, and the lack of universal eligibility criteria for certain multi-organ combinations are hurdles that need to be tackled in the future.
Keywords: liver transplantation; combined transplantation; allocation; immunotolerance; machine perfusion